PERANAN PENUNTUT UMUM DALAM ASPEK PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA NARKOTIKA (PENGUNGKAPAN PELAKU DENGAN TEKNIK PEMBELIAN TERSELUBUNG) - Trynalia (2022)
Narcotics is an extraordinary crime. In addition to the negative impact it causes, the disclosure of narcotics crimes is not easy because it is transnational in nature, is carried out in secret, is organized, uses various modus and uses advanced technology. Therefore, Law Number 35 of 2009 regulates investigation techniques that can be used to uncover narcotics crimes. One of them is a undercover buy, as regulated in Article 75 letter j. Act. With this technique, investigators can be directly involved with various roles until finally the perpetrator is caught along with the evidence. However, in case handling, there are obstacles to proving criminal responsibility aspect of perpetrator. This research aims to analyze the obstacle and the role of Public Prosecutor in proving criminal responsibility aspect of narcotics crime perpetrator which is releaved through undercover buy method. The type of research is a normative research type by analyzing secondary data. This research explains the various obstacles faced by the Public Prosecutor which come from internal factor or external factor and the role that has not been maximized in terms of revealing the perpetrators of narcotics crimes with undercover buy